Diagnostic Test of Blood Eosinophil Level as a Marker of Ascaris lumbricoides Infection - Said Munazar Rahmat; Teuku Romi Imansyah Putra; Merina Panggabean; Aman Agustinus Depari; Dhiatama Endalif (Institute of Topical Disease Universitas Airlangga, 2023)
A. lumbricoides infection is one from 17 neglected tropical diseases in Indonesia. But, Infection of A. lumbricoides in Indonesia often undiagnosed. This is because stool examination with Kato-Katz's method still rarely done. So it needs something alternative examination that more practical and can be routinely carried out. This study was a diagnostic test for blood eosinofil levels in diagnosing A. lumbricoides infection. This research was conducted at a hospital in Medan. This study involved 63 children who had their parents approval. Children stool were examined by Kato-Katz method as a gold standard and blood eosinofil levels was examined as an index in this study. The results showed sensitivity level of eosinofil is 25% and specificity 96,08%, positive predictive value 60%, negative predictive value 84%, positive likelihood ratio 6,38% and negative likelihood ratio 0,78%. The conclusion is elevated blood eosinofil levels cannot be used as an alternative test Kato-Katz in diagnosing Infection of A. lumbricoides.